Factors Associated with Nurses’ Knowledge in Carrying Out Cardiopulmonary Resuscitation (CPR) - Jufrizal; Fikriyanti; Aklima; Irfanita Nurhidayah (Fakultas Keperawatan Universitas Andalas, 2025)
Cardiopulmonary resuscitation (CPR) is the first effort or action taken to maintain life when a sufferer experiences a situation that threatens a person who experiences respiratory arrest and cardiac arrest who still has hope for life if the health team is alert in treating the victim and providing first aid to the victim. The aim of this study was to identify factors related to nurses' knowledge in carrying out cardiopulmonary resuscitation. This research uses quantitative and correlative types. The sample in this study was 52 nurses who worked in the intensive care unit at Banda Aceh City Hospital. The results of this research are that there is no relationship between age and nurses' knowledge in carrying out CPR (p-value 0.828), there is a relationship between education and nurses' knowledge in carrying out CPR (p-value 0.000), there is a relationship between experience and nurses' knowledge in carrying out CPR (p-value 0.039), there is a relationship between facilities and nurses' knowledge in carrying out CPR (p-value 0.000). The sufficient knowledge of CPR among nurses underscores the need for continuous training and regular skills assessments. Strengthening CPR education in hospitals ensures prompt, effective responses in emergencies, improving patient safety and cardiovascular outcomes in critical care.